Ultra-high pressure decontamination of insect biocontrol preparations - Butz, Peter; Fritsch, E.; Huber, J.; Keller, B.; Ludwig, Horst; Tauscher, Bernhard (Biocontrol science and technology, 1995)
Living bacteria or bacterial spores are undesirable components of baculovirus preparations (e.g. granulosis virus) produced in vivo. This is also true, at least in Germany, for preparations of Bacillus thuringiensis subsp. tenebrionis. Using ultra-high pressure treatment (at a pressure of 550-580 MPa and a temperature of 50 C) the concentration of these bacterial contaminants was reduced by up to eight orders of magnitude. The biocontrol activity of both preparations remained unchanged.
Online veröffentlicht: 28. Juni 2010
Gesehen am 15.01.2026